Surface damage resistance and yielding of chemically strengthened silicate glasses: From normal indentation to scratch loading - Sani, Gohar; Limbach, Rene; Dellith, Jan; Sokmen, Ilkay; Wondraczek, Lothar (Journal of the American Ceramic Society, 2021)
We report on surface elasticity, plastic deformation and crack initiation of chemically strengthened soda-lime silicate and sodium aluminosilicate glasses during lateral indentation and scratch testing. Instrumented indentation using a normal indenter set-up corroborated previous findings on the effects of chemical strengthening on surface Young's modulus, hardness, and indentation cracking. Using lateral indentation in the elastic-plastic regime, we find a pronounced increase in the scratch hardness as a result of chemical strengthening, manifest in higher work of deformation required for creating the scratch groove. Thereby, the glass composition is found to play a stronger role than the absolute magnitude of surface compressive stress. Using a blunt conical stylus for instrumented scratch testing reveals three distinct modes of scratch-induced surface fracture, which occur during scratching or after unloading. Occasional micro-cracking caused by pre-existing surface flaws at low scratching load can be completely suppressed through chemical strengthening. The intrinsic defect resistance to microcracking is reduced as a result of ion stuffing, depending on the initial glass composition, whereas the resistance to abrasive yielding is enhanced by several hundred MPa.
CRIS-Team Scopus Importer:2023-04-20
Keywords: abrasive wear; chemical strengthening; crack resistance; glass; hardness; indentation; mechanical properties; scratching